Nurses' Knowledge and Skills Regarding Care Bundle guideline in Mosul Hospitals - Adel Yousif Ayed AL-Moutiwty; Mohammed Ahmed Sultan AL-Wily (Kufa Journal for Nursing Sciences)
Objective: This study aimed to assess the knowledge levels and skills regarding care bundle guidelines among nurses in Mosul hospitals.